Global futures of energy, climate, and policy: qualitative and quantitative foresight towards 2055 - Ansari, Dawud; Holz, Franziska; Tosun, Hasan Basri (Berlin, 2019)
"Existing long-term energy and climate scenarios are typically a rather simple extrapolation of past trends. Both qualitative and quantitative outlooks co-exist, but they often focus narrowly on individual perspectives, which is opposed to the interlinked and complex nature of energy and climate. Therefore, this study presents a set of novel and multidisciplinary narratives that give insight into four distinct and extreme yet plausible worlds: base case ‘Business-as-usual’, worst case ‘Survival of the Fittest’, best case ‘Green Cooperation’, and surprise scenario ‘ClimateTech’. Going beyond other outlooks, our narratives focus on changes in the geopolitical landscape and global order, social perspectives on climate issues, and technological progress. These holistic scenarios are designed to overcome previous barriers by an innovative bridging between both qualitative and quantitative methods. We start with the generation of qualitative scenario storylines using techniques of foresight analysis, including a facilitated expert workshop. Then, we calibrate the numerical energy systems model Multimod to reflect the different storylines. Finally, we unite and refine storylines and numerical model results into holistic narratives. In addition to the narratives (which include quantitative results on e.g. emissions, energy consumption, and the electricity mix), the study generates insights on the key uncertainties and drivers of different pathways of (more or less successful) climate change mitigation. Additionally, a set of transparent indicators serves as an early-warning system to identify which of the paths the world might enter. Lessons learnt include the dangers from increased isolationism and the importance of integrating economic and energy-related objectives as well as the large role of public opinion and social transition."